'Mother says I'm just an odd duck': Alan Turing, The Imitation Game and the 'gay boffin'. Issue 1 (1st March 2019) - Robinson, Matthew
The legacy of mathematician Alan Turing comprises both his contribution to the British war effort decrypting the German Enigma code at Bletchley Park and his treatment after the war, when he was convicted of gross indecency, underwent hormonal therapy and committed suicide. The Imitation Game (Tyldum, 2014), a 'prestige' biopic about his life, negotiates Turing's problematic legacy as both war hero and gay martyr by modelling him through the 'boffin' stereotype present in British films about scientists. The boffin's key characteristic is his 'outsider' status and the biopic reworks this to construct Turing as an outsider in different communities – at Sherborne School, within the code-breaking team at Bletchley but also, due to contemporary homophobic legislation, in wider British society. This article examines The Imitation Game's depiction of Turing as 'gay boffin', how it negotiates the different histories that Turing's life embodies and how film reviewers criticized The Imitation Game for its lack of scenes depicting gay relationships. Unlike other contemporary efforts that challenged the suppression of Turing's homosexuality in public memory, The Imitation Game's gay boffin instead exemplifies a continued anxiety with Turing's legacy as a homosexual war hero.